The Brief Experiential Avoidance Questionnaire: A Viable Alternative to aaq-ii? - Valencia, Pablo D. (Pensando Psicología, 2018)
Introduction: Experiential avoidance ( ea ) is a central concept in the study of psychopathology from acontextual-behavioral perspective. The Acceptance and Action Questionnaire ii ( aaq - ii ) has become themost commonly used measure of ea . However, some authors have seriously questioned its validity. Inthis context, the Brief Experiential Avoidance Questionnaire ( beaq ) is a promising alternative.Aim: The present study intended to translate the beaq into Spanish and analyze its psychometric prop-erties in a Peruvian sample.Materials and methods: The beaq was back-translated and a group of experts assessed the quality ofthe items. The questionnaire was responded by 376 Peruvian university students. The beaq - ii itemswere then subjected to an exploratory factorial analysis. Reliability estimators (H, α, ωT, ωTR) werealso calculated.Results: The results did not support the supposed unidimensional nature of the beaq . Moreover, theysuggested the presence of two factors called Avoidance of Suffering and Disconnection and Deacti-vation. Only the Avoidance of Suffering factor showed good reliability and could be easily interpreted.Conclusion: Future research should develop a new measure of ea based on the items of the Avoidanceof Suffering factor. It is suggested that researchers continue to use aaq - ii until better measures of ex-periential avoidance are available.
Keywords: AAQ-II; exploratory factor analysis; acceptance and action questionnaire; experiential avoidance